First-in-human, phase 1 study of PF-06753512, a vaccine-based immunotherapy regimen (VBIR), in non-metastatic hormone-sensitive biochemical recurrence and metastatic castration-resistant prostate cancer (mCRPC). Issue 3 (22nd March 2023) - Autio, Karen A; Higano, Celestia S; Nordquist, Luke; Appleman, Leonard J; Zhang, Tian; Zhu, Xin-Hua; Babiker, Hani; Vogelzang, Nicholas J; Prasad, Sandip M; Schweizer, Michael T; Madan, Ravi A; Billotte, Stephane; et al.
Abstract : Background: This phase 1 study evaluated PF-06753512, a vaccine-based immunotherapy regimen (PrCa VBIR), in two clinical states of prostate cancer (PC), metastatic castration-resistant PC (mCRPC) and biochemical recurrence (BCR). Methods: For dose escalation, patients with mCRPC received intramuscular PrCa VBIR (adenovirus vector and plasmid DNA expressing prostate-specific membrane antigen (PSMA), prostate-specific antigen (PSA), and prostate stem cell antigen (PSCA)) with or without immune checkpoint inhibitors (ICIs, tremelimumab 40 or 80 mg with or without sasanlimab 130 or 300 mg, both subcutaneous). For dose expansion, patients with mCRPC received recommended phase 2 dose (RP2D) of PrCa VBIR plus tremelimumab 80 mg and sasanlimab 300 mg; patients with BCR received PrCa VBIR plus tremelimumab 80 mg (Cohort 1B-BCR) or tremelimumab 80 mg plus sasanlimab 130 mg (Cohort 5B-BCR) without androgen deprivation therapy (ADT). The primary endpoint was safety. Results: Ninety-one patients were treated in dose escalation (mCRPC=38) and expansion (BCR=35, mCRPC=18). Overall, treatment-related and immune-related adverse events occurred in 64 (70.3%) and 39 (42.9%) patients, with fatigue (40.7%), influenza-like illness (30.8%), diarrhea (23.1%), and immune-related thyroid dysfunction (19.8%) and rash (15.4%), as the most common. In patients with mCRPC, the objective response rate (ORR, 95% CI) was 5.6% (1.2% to 15.4%) and the median radiographic progression-free survival (rPFS) was 5.6 (3.5 to not estimable) months for all; the ORR was 16.7% (3.6% to 41.4%) and 6-month rPFS rate was 45.5% (24.9% to 64.1%) for those who received RP2D with measurable disease (n=18). 7.4% of patients with mCRPC achieved a ≥50% decline in baseline PSA (PSA-50), with a median duration of 4.6 (1.2–45.2) months. In patients with BCR, 9 (25.7%) achieved PSA-50; the median duration of PSA response was 3.9 (1.9–4.2) and 10.1 (6.9–28.8) months for Cohorts 5B-BCR and 1B-BCR. Overall, antigen specific T-cell response was 88.0% to PSMA, 84.0% to PSA, and 80.0% to PSCA. Conclusions: PrCa VBIR overall demonstrated safety signals similar to other ICI combination trials; significant side effects were seen in some patients with BCR. It stimulated antigen-specific immunity across all cohorts and resulted in modest antitumor activity in patients with BCR without using ADT. Trial registration number: NCT02616185 .